Some atmospheric trace metals deposition in selected trees as a possible biomonitor (Romanian Biotechnological Letters, 2024)
Several trees are effectively used to biomonitor of trace metals in urban environmental pollution. It gives information about the speciation of trace metals  and their transition between organs in the plant. In the wood of the trees, it can be determined which part is formed in which year with the help of organs formed by  the effect of seasonal differences. Air pollutants damage to humans and other  living things in nature is generally referred to as a sign of pollution. They are  released from anthropogenic sources accumulate in the bodies of nearby species  over time. They give information about the history of air pollutants due to the accumulation in their wood, inner bark, and outer bark. In this study, organs of  Robinia pseudoacacia L., Cupressus arizonica G., and Platanus orientalis L. were  analyzed as biomonitors with Inductively Coupled Plasma Mass Spectrometry (ICP- MS). All samples were taken from Kocaeli province industrial zone which has quite  a wide industrial area. The concentration of selected trace elements as Iron (Fe),  Magnesium (Mg), and Zinc (Zn) their emission caused by industrial activities and  transport vehicle density. The results of the study show that Robinia pseudoacacia  L. was the most suitable species for Fe, Mg, and Zn concentration levels as a  biomonitor.
Keywords: Atmospheric deposition; biomonitor; trace elements; trees